2007
DOI: 10.1016/s1808-8694(15)31136-8
|View full text |Cite
|
Sign up to set email alerts
|

Cheilitis granulomatosa associated with melkersson-rosenthal syndrome

Abstract: Melkersson-Rosenthal syndrome (MRS) consists of persistent or recurrent orofacial edema, relapsing facial palsy and fissured tongue. The complete triad of symptoms is uncommon, varying from 8 to 25%. The presentation of only one symptom is more common. The most frequent complaint is facial edema and enlargement of the lips. We describe a case of a 17-year-old Brazilian girl with limited edema of the lower lip and fissured tongue due to MRS. Her complaints had started two years before. She referred previous cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 6 publications
0
12
0
1
Order By: Relevance
“…Regarding familiar occurrence of deafness in association with skin diseases, Heathcote et al reported a three generation family with an autosomal dominant syndrome of sensorineural hearing loss and palmoplantar hyperkeratosis, which has been regarded as a distinct clinical entity (MIM number 148350). 5 Although previously not reported in association with sensoneurinal deafness, it is possible that EC and TS resulted from the same underlying genetic abnormalities that lead to hyperproliferative tendency of this patient's epidermis leading to plugging of the follicular orifices and hearing impairment. Speculation is based on very similar skin phenotype in close relatives connected with hearing impairment.…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…Regarding familiar occurrence of deafness in association with skin diseases, Heathcote et al reported a three generation family with an autosomal dominant syndrome of sensorineural hearing loss and palmoplantar hyperkeratosis, which has been regarded as a distinct clinical entity (MIM number 148350). 5 Although previously not reported in association with sensoneurinal deafness, it is possible that EC and TS resulted from the same underlying genetic abnormalities that lead to hyperproliferative tendency of this patient's epidermis leading to plugging of the follicular orifices and hearing impairment. Speculation is based on very similar skin phenotype in close relatives connected with hearing impairment.…”
mentioning
confidence: 82%
“…Sussman et al 4 showed complete remission in five of the 11 patients with CG following the treatment. Ratzinger et al 5 observed complete or partial response in majority of patients treated with clofazimine. Unfortunately we have no experience with this drug.…”
Section: Editormentioning
confidence: 97%
See 1 more Smart Citation
“…Also, localization on the upper lip causes a proboscis-like malformation called 'tapirus mouth' [46]. Gonçalves et al [47] reported a 17 years old patient with continuing swelling of the lips with fissured tongue due to MRS. Recent studies have considered MRS as the first sign of Crohn's disease, therefore, these patients should be screened and observed for gastrointestinal symptoms.…”
Section: Melkersson-rosenthal Syndromementioning
confidence: 99%
“…[ 1 ] However, the monosymptomatic form is more common and typical manifestation is facial edema and/or enlargement of lips. [ 2 ]…”
mentioning
confidence: 99%